STRUCTURAL RELATIONSHIP OF THE BRAIN - Kattaxodjayeva Dinara Utkurxodjayevna; Ibragimova Gulzira Janabayevna (Proximus Journal Publishing, 2025)
The paper examines the projection, sagittal section of the brain. It is shown that the newest method for studying brain activity consists of measuring and recording electrical potentials, or waves, that occur in different parts of the brain. During sleep, the body restores the energy expended during the day; voluntary muscles relax, and some involuntary muscles, such as respiratory muscles, slow down their work.
Keywords: brain; energy; wave; recording